Widespread clinical implementation of the teen online problem-solving program: Progress, barriers, and lessons learned - Wade, Shari L.; Walsh, Kathleen; Slomine, Beth S.; Davis, Kimberly C.; Heard, Cherish; Maggard, Brianna; Sutcliffe, Melissa; Van Tubbergen, Marie; McNally, Kelly; Deidrick, Kathleen; Kirkwood, Michael W.; Lantagne, Ann; et al. (Frontiers in Rehabilitation Sciences, 2023)
Objective: We describe the clinical implementation in North America of Teen Online Problem Solving (TOPS), a 10+ session, evidence-based telehealth intervention providing training in problem-solving, emotion regulation, and communication skills. Methods: Twelve children’s hospitals and three rehabilitation hospitals participated, agreeing to train a minimum of five therapists to deliver the program and to enroll two patients with traumatic brain injuries (TBI) per month. Barriers to reach and adoption were addressed during monthly calls, resulting in expansion of the program to other neurological conditions and extending training to speech therapists. Results: Over 26 months, 381 patients were enrolled (199 TBI, 182 other brain conditions), and 101 completed the program. A total of 307 therapists were trained, and 58 went on to deliver the program. Institutional, provider, and patient barriers and strategies to address them are discussed. Conclusions: The TOPS implementation process highlights the challenges of implementing complex pediatric neurorehabilitation programs while underscoring potential avenues for improving reach and adoption.